5-Bromoisoxazolidines: synthesis, reactivity and NMR study. (27th April 2021) - Záborský, Ondrej; Malatinský, Tomáš; Štadániová, Radka; Kalník, Martin; Doháňošová, Jana; Moncol, Ján; Fischer, Róbert
Graphical abstract: Highlights: New 5-bromoisoxazolidines were prepared. NMR study of the formation of 5-bromo-4-hydroxyisoxazolidine is presented. Reactivity of the new isoxazolidines was studied. Abstract: The synthesis of novel 4, 5-dibromoisoxazolidines is described. Their reactivity was compared with the similar 5-bromo-4-hydroxyisoxazolidine via the use of simple experiments such as methanolysis and azidation. Moreover, the structures of both prepared diastereoisomers of 5-azido-4-hydroxyisoxazolidine were confirmed by X-ray crystallographic analysis. Finally, an NMR study of the formation and anomerization of 5-bromo-4-hydroxyisoxazolidine from the corresponding isoxazolidinyl epoxide is presented.